Pemanfaatan Hasil Samping Tepung Tulang Ikan Bandeng (Chanos chanos) Menjadi Produk Added Value Berupa Cookies - Simamora, Gevbry Ranti Ramadhani; Hidayat, Jefri Pandu (Universitas Negeri Gorontalo, 2024)
Fish bone can be utilized as an additional ingredient in food processing. Cookies are one of the processed dry cakes that utilize the nutritional content found in the by-products of milkfish bones, thus becoming an alternative snack for osteoporosis patients. The common process of milkfish bone processing is grinding, which can be added to Cookies products. Cookies are sweet dry cakes made from wheat flour. Cookies, as dry food products, have a relatively long shelf life, thus maintaining product durability (approximately up to one year) and are easy to carry due to their small volume and weight resulting from the drying process. The aim of this research is to determine the effect of milkfish bone processing on the flour content and Cookies on proximate content, protein content, moisture content, ash content, and calcium and phosphorus content in milkfish bone flour cookies. The research method was conducted using an experimental method with two treatments, namely chocochip cookies and savory cookies, which were analyzed using one-way Anova in the XLStat software. The results showed that fortified milkfish bone chocochip cookies had nutritional content such as moisture content (0.72%); ash (4.18%); protein (7.26%); fat (27.33%); carbohydrates (60.51%); calcium (0.14%); phosphorus (0.12%), and the nutritional content of savory cookies fortified with milkfish bone had nutritional content such as moisture content (7.83%); ash (1.83%); protein (4.33%); fat (28.46%); carbohydrates (57.70%); calcium (0.18%); phosphorus (0.17%).